Integrated analysis of tyrosine-induced MiRNA and mRNA expression profiles in melanocytes reveals the regulatory role of miR-1560-3p in melanin deposition in Xichuan black-bone chickens - Zhiyuan Zhang; Pengwei Zhang; Fumin He; Yingdong Hou; Xiaowen Geng; Ruilong Xu; Ruiting Li; Yadong Tian; Wenting Li; Guirong Sun; Ruirui Jiang; Xiaojun Liu; et al. (BMC Genomics)
Abstract Background Tyrosine is a prerequisite for melanin biosynthesis and plays a crucial role in the growth and development of melanocytes, but the underlying mechanism is still unclear. In our previous research, we added 10− 9-10− 6 mol/L tyrosine to the melanocytes of black-bone chickens and found that 10− 6 mol/L tyrosine significantly increased the tyrosinase content in melanocytes. Methods In this study, melanocytes from Xichuan black-bone chickens were used as research objects, 10− 6 mol/L tyrosine was added for transcriptome sequencing. By analyzing miRNA and mRNA expression profiles, the miRNA-mRNA network was constructed, the targeting relationship was demonstrated by double luciferase reporting experiments, and the influence of tyrosine-mediated miRNA-mRNA network on melanin deposition was verified by constructing overexpression and interference vectors. Results We found that tyrosine promoted the proliferation and migration of melanocytes, and expression profile analysis identified 57 differentially expressed mRNAs (DEGs) and 19 differentially expressed miRNAs (DEMs). Fifty miRNA‒mRNA target gene pairs were identified via coexpression network analysis of the DEGs and the DEMs that were predicted to target various genes. Notably, VIP gene was reported to be involved in the development and deposition of melanoma cells. The binding of VIP to miR-1560-3p was further validated by a dual-luciferase reporter assay. In addition, test confirmed that miR-1560-3p inhibited the proliferation and migration of melanocytes and reduced the tyrosinase content. In conclusion, we found that tyrosine may affects melanin deposition in Xichuan black-bone chickens by affecting the miR-1560-3p-VIP axis. The results of this study provide experimental evidence for elucidating the mechanism of tyrosine in melanin deposition in black-bone chickens, and may serve as a reference for future investigations.